Kebutuhan dan Larangan Kudeta Perspektif Hadits Hadits Siyasah - Dr.Aripin Marpaung; Kelas Htn 5c (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the necessity and prohibition of coups from the perspective of hadith siyasah, focusing on the normative foundations of political authority and stability in Islamic teachings. Employing a qualitative library research approach, the study analyzes selected hadiths related to leadership, obedience to legitimate rulers, prohibition of rebellion, and the preservation of social unity. The data were collected from authoritative hadith compilations and contemporary scholarly works published after 2019, and analyzed through descriptive-analytical methods. The findings indicate that Islamic teachings strongly prohibit coups as acts of forced power seizure due to their potential to cause social disorder, disunity, and harm to the public interest. At the same time, the hadiths acknowledge the necessity of political correction and reform, provided that such efforts are conducted through ethical and peaceful means, such as advice, consultation, and amar ma’ruf nahi munkar. This study concludes that the prohibition of coups in hadith siyasah is not intended to legitimize unjust governance, but rather to safeguard political stability and social welfare in accordance with the objectives of Islamic law (maqasid al-shari‘ah). The findings contribute to contemporary discussions on Islamic political thought by highlighting a balanced approach between justice and stability in governance.